MENGENAL ETOS KERJA BANGSA JEPANG: LANGKAH MENGGALI NILAI-NILAI MORAL BUSHIDO BANGSA JEPANG - Iriyanto Widi Suseno (KIRYOKU, 2017)
The focus of this research is the ethos of the work of the Japanese nation that is studied in the perspective of the moral values of Japanese Bushido. The goal is to find the moral values of Bushido that form the work ethos of the Japanese nation. This study uses descriptive qualitative methods, namely by analyzing the Japanese cultural structure to find the moral values of Bushido. Then eclectically compresses it into meaningful systematic strata and unity. Hasisl research describes, the work ethic profile of the Japanese people have: integrity, courage, generous, respect and courteous to others, honest and sincere, sincere, good name and honor, loyalty to leaders and caring. The overall values of Bushido's moral values are already owned by Indonesian culture since our ancestors. The results of this study provide function as a strengthening, and revalidation of Indonesian culture that is currently experiencing cultural distortion and moral values of the nation.